AN ANALYSIS OF FACTOR THAT INFLUENCE THE INTERESTS IN BEHAVIORS OF USING ACCOUNTING INFORMATION SYSTEMS BASED ON E-COMMERCE - Izzati, Rosyida Rahma; Muntiah, Nur Saydatul; Hidayah, Nurul (Politeknik Negeri Madiun, 2020)
This study aims to analyze: 1) the influence of attitude on behavioral interest, 2) the influence of subjective norms on behavioral interest, 3) the influence of perceptual behavioral control on behavioral interest, 4) the influence of ease use of perception on behavioral interest and 5) the influence of the usefulness of perception on behavioral interest. There are 160 respondents in this study. They are the users of accounting information systems based on e-commerce. This study uses multiple linear regression research methods. Based on the results of the instruments can be seen that all items are valid and reliable statement. The results of the study showed that: 1) there is an influence of attitude on behavioral interest, 2) there is an influence of subjective norms on behavioral interest, 3) there is an influence of perceptual behavior control on behavioral interest, 4) there is an influence of ease of use of perception of behavioral interest and 5) there is an influence of usefulness of perception on behavioral interest.